What I learned in school : reflections on race, child development, and school reform - Comer, James P. (Outstanding ideas in education., 2009)
James P. Comer began his extraordinary life's journey from his hometown of East Chicago, Indiana. While his childhood friends languished in jail or faced early deaths from alcoholism, Comer went on to become a medical doctor, child psychologist, acclaimed leader of education reform, and expert on race relations. What I Learned in School highlights, in one volume, the major contributions of world-renowned scholar Dr. James P. Comer, whose visionary work has dramatically shaped the fields of school reform, child development, psychology, and race. This small collection of Dr. Comer's work is beautifully arranged and includes an introduction and engaging updates from the author. These works paint a remarkable picture of what we've all learned so far, and what we all must learn going forward. The excerpts presented in this collection span Dr. Comer's remarkable career and include selections from his best-selling book Maggie's American Dream to the influential Leave No Child Behind. At the very heart of the lessons learned is the idea that the most efficient and effective way to meet the needs of our students would be to prepare our education workforce to integrate student development and academic learning in all aspects of learning from school entry through student maturity. Dr. Comer puts the focus on promoting student personal responsibility in preparation for meeting life tasks. As the book clearly reveals, James Comer's life and work has been an endless quest to answer one persistent question: Why not prepare a workforce to support the development of the whole child? --Publisher's description.